On the Periodicity of Some Classes of Systems of Nonlinear Difference Equations - Stevo Stević; Mohammed A. Alghamdi; Dalal A. Maturi; Naseer Shahzad (Abstract and Applied Analysis)
Some classes of systems of difference equations whose all well-defined solutions are periodic are presented in this note.